1994
DOI: 10.1002/pen.760340110
|View full text |Cite
|
Sign up to set email alerts
|

Relating the heat‐of‐mixing of analog mixtures to the miscibility of hydrogen‐bonding polymers

Abstract: The prediction of polymer/polymer miscibility is addressed using analog calorimetry and molecular modeling. For each polymer, an analog compound representing one or two repeat units was chosen. Heat‐of‐mixing was measured for liquid mixtures of analog compounds and then used in a binary interaction model to predict polymer miscibility. Specifically, we have measured exothermic heats‐of‐mixing for 4‐ethyl phenol, an analog of poly(vinly phenol), with several analogs containing ether, ester, or ketone functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Although quantitatively the values obtained from analog mixtures are quite different to those reported in Tables 2 and 3, qualitative information about the exothermic or endothermic nature of the interactions between polymer repeat units can be obtained from the analog compound mixtures. In fact, reasonable agreement is found between data from copolymer blends and analog mixtures, taking into account that intramolecular connectivity and other macromolecular effects [31,32] are absent in low molecular weight model compound mixtures.…”
Section: Determination Of Temperature-dependent Segmental Interactionsupporting
confidence: 66%
“…Although quantitatively the values obtained from analog mixtures are quite different to those reported in Tables 2 and 3, qualitative information about the exothermic or endothermic nature of the interactions between polymer repeat units can be obtained from the analog compound mixtures. In fact, reasonable agreement is found between data from copolymer blends and analog mixtures, taking into account that intramolecular connectivity and other macromolecular effects [31,32] are absent in low molecular weight model compound mixtures.…”
Section: Determination Of Temperature-dependent Segmental Interactionsupporting
confidence: 66%
“…It has also been found that the interassociation between polymers is affected by the structure of estercontaining polymers. 25,26 In view of the total mis-cibility of PVPh with PPL, 19 PCL, 19 and PHB 22,23 via interassociation, it is of interest to study the miscibility of PDLLA/PVPh blends.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting terpolymer has a lower crystallinity and lower melting point, and it is tougher and more processable . At the same time, PK‐based blends with polypropylene, poly(vinylphenol), polyester, and polyamide have been successfully prepared, showing a good compatibilization level and a generally increasing thermal stability. Composites with calcium carbonates and nanocomposites with layered clay, both organomodified, increased the mechanical performance of PK with particular reference to toughening effects and the flexural strength.…”
Section: Introductionmentioning
confidence: 99%